All for One: Contributions of Age, Socioeconomic Factors, Executive Functioning, and Social Cognition to Moral Reasoning in Childhood - Vera-Estay, Evelyn; Seni, Anne G.; Champagne, Caroline; Beauchamp, Miriam H. (Frontiers in Psychology, 2016)
Moral reasoning (MR) is a sociocognitive skill essential to appropriate social functioning in childhood, and evolves in quality and complexity during ontogenetic development. Whereas past research suggests that MR is related to age, socioeconomic factors, as well as some social and cognitive skills, such as executive functioning, theory of mind, empathy, and affect recognition, their contributions have been studied in silos rather than comprehensively, with little integration of the relative and combined contribution of these skills to MR. Furthermore, few studies have addressed the putative links between these factors in childhood, a period during which these skills are in maturation. The aim of this study was to explore what factors predict moral maturity in typically developing children (n=76, 47.4% males, M = 9.2, SD = 1.67 years), explore the potential moderating and mediating role of executive functions and social cognition in the relationship between age and MR maturity, and identify the specific contributions of age, socioeconomic factors, executive functioning and social cognition, using an innovative visual MR assessment tool (So-Moral). The results indicate that MR maturity was correlated with age, executive functioning (inhibition, verbal fluency, and attentional control) and social cognition (theory of mind and affect recognition). Neither EF nor social cognition moderated the effect of age on MR maturity. However, verbal fluency and third-order false beliefs had a moderating role in this link. MR maturity in children was predicted by three variables from each of the three domains: age, verbal fluency and third order theory of mind. These results contribute to a better understanding of the underpinnings of MR during childhood, suggesting that MR is not reducible to general developmental factors such as age, but that higher order skills such executive functioning and social cognition also contribute to moral maturity. The findings have relevance for both typically developing and clinical populations in which social skills may be reduced, as well as for the identification of potential loci for intervention in children at-risk for socially maladaptive behaviors.